Respostas

A melhor resposta!
2014-06-06T11:23:32-03:00
A) 4x² - 6 +2= 0 
Δ= (-6)² - 4.4.2
Δ= 36- 32 = 4 

x= +6 +/- √4 
         2.4 
x'=  6+2= 8 = 1 
       8     8
x''= 6-2/ 8 = 4/8 = 0,5 

b) 12x²+x-1=0 

Δ= 1² - 4.12.(-1)
Δ= 1 + 48= 49 

x= -1+/-√49
        2.12

x'= -1+7= 6 = 0,25
       24    24 

x''= -1-7 = -8= 0,33
       24     24
      


2 5 2
2014-06-06T11:40:14-03:00
A) 4x²-6+2=0, p/ a = 4 // b = -6 // c = 2
Δ = b² - 4ac = (-6)²-4(4)(2) = 36 - 32 = 4
x´ = (-b + √Δ)/2a = [-(-6) + 2]/8 = 8/8 = 1
x" = (-b - √Δ)/2a = [-(-6) - 2]/8 = 4/8 = 1/2
S = {1/2, 1}
.................................... 
B) 12x²+x-1=0, p/ a = 12 // b = 1 // c = -1
Δ = b² - 4ac = (1)²-4(12)(-1) = 1 + 48 = 49
x´ = (-b + √Δ)/2a = (-1 + 7)/24 = 6/24 = 1/4
x" = (-b - √Δ)/2a = (-1 - 7)/24 = -8/24= -1/3
S = {-1/3, 1/4}
2 4 2